Collective memory: between individual systems of consciousness and social systems - Orianne, Jean-François; Eustache, Francis (Frontiers in Psychology, 2023)
Following a long period of neglect, research on different facets of collective memory is now developing apace in the human and social sciences, as well as at their interface with psychology and neuroscience. This resolutely multidisciplinary renewal of interest in memory sciences has given rise to a plethora of concepts with diverse meanings (e.g., social frameworks of memory, collective, shared, collaborative, social memory). The purpose of the present study was to provide a conceptual overview from a historical perspective, and above all to clarify concepts that are often used interchangeably, even though they refer to very different realities. Based on recent research in psychology and neuroscience, we use the concept of collective memory to refer to the operations of individual systems of consciousness. Collective memory is not the memory of a collective, but that of its individual members, either as members of social groups (shared memory) or as participants in social interactions (collaborative memory). Drawing on the contributions of contemporary sociology, we show that social memory is not collective memory, as it refers not to individual systems of consciousness, but to social systems. More specifically, it is the outcome of communication operations which, through redundancy and repetition, perform a continuous and selective re-imprinting of meaning that can be used for communication. Writing, printing and the new communication technologies constitute the three historical stages in the formation and development of an autonomous social memory, independent of living memories and social interactions. In the modern era, mass media fulfill an essential function of social memory, by sorting between forgetting and remembering on a planetary scale. When thinking about the articulation between collective memory and social memory, the concept of structural coupling allows us to identify two mechanisms by which individual systems of consciousness and social systems can interact and be mutually sensitized: schemas and scripts, and social roles. Transdisciplinary approach spearheads major methodological and conceptual advances and is particularly promising for clinical practice, as it should result in a better understanding of memory pathologies, including PTSD, but also cognitive disorders in cancer (chemobrain) or in neurodegenerative diseases.